INFECTIOUS DISEASES COMPLICATED BY HEMOPHAGOCYTIC LYMPHOHISTIOCYTOSIS – A RARE CASE SERIES - CHHABRA, AJAY; KHATTAR, SALONI; BAGGA, PERMEET (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Hemophagocytic lymphohistiocytosis (HLH) is a rare, yet potentially fatal disorder of uncontrolled inflammation and dysregulated immunity. Patients may present with features ranging from fever, rash, and cytopenias to fatal multiorgan failure. Here, we present a case series reporting four cases of HLH, their clinicopathological findings, laboratory investigations, and outcomes. The underlying causes for the four cases were found to be infective ones, i.e., Leptospira, hepatitis-E and herpes simplex virus-1, kala-azar and malaria and enteric fever. HLH is a manifestation of the dysregulated immune response of various T cells leading to cytokinemia causing an accumulation of macrophages and T lymphocytes in various tissues. Infections account for about half of all HLH cases in adults the world over. In our institute, infections may still be more prevalent as a cause. Moreover, this may be the scenario in our country where infectious diseases remain a major proportion of the disease burden.